Exhibition on biodiversity in an outdoor setting and reflections on the action taken (Research, Society and Development, 2024)
The benefits of science are well-known, and it is essential to understand scientific knowledge as a tool for achieving social well-being. Given the importance of environmental studies for life preservation on Earth, the aim of this work was to reflect on the potential of an educational exhibition on animal biodiversity, linked to the Sustainable Development Goals (SDGs), as a way to engage the external audience in an interactive exchange of environmentally connected knowledge. The methodology, of a qualitative nature, involved: (a) planning and research on lesser-known animal groups to contextualize in the exhibition, alongside the 17 SDGs, in an outdoor setting; (b) the creative setup and display of informational materials on biodiversity and the SDGs for external groups; (c) monitoring the stages of the process with the students involved; (d) evaluation of the effectiveness of the innovative elements experienced. The opportunities for dialogic interactions with the external public enriched the educational scenario, promoting differentiated learning throughout the training path.